Characteristics of climate resource utilization and economic benefits in new planting pattern for fresh faba bean and fresh maize in Yangtze River Delta - Bo Li; Qingming Ren; Xiaoxu Shi; Wenyuan Shen; Yafeng Wei; Fei Xiong (Plant Production Science)
In this research, we aimed to construct a novel planting pattern for faba bean and maize with high-efficiency utilization of climate resources for application in production. We incorporated relay intercropping in two triple-crop planting patterns, namely faba bean/maize-maize and faba bean/maize-soybean. A field experiment was conducted to compare the annual yield, utilization efficiency of climatic resources and economic benefits among these two triple-crop planting patterns and the conventional faba bean – maize double-cropping system at Nantong, Jiangsu, China, from 2016 to 2020. Compared with the conventional double-cropping system, the faba bean/maize-maize triple-crop planting pattern resulted in significantly increased annual yield by 7,392 kg hm−2 to 10,519 kg hm−2, and increased annual biomass by 5,342 kg hm−2 to 7,172 kg hm−2.The triple-crop planting patterns increased the annual economic benefit by 12,195 RMB hm−2 and 15,680 RMB hm−2, respectively. The faba bean/maize-maize triple-crop planting pattern increased the annual radiation production efficiency by 0.18 g·MJ−1 to 0.31 g·MJ−1, the annual temperature production efficiency by 2.70 kg·hm−2·°C−1 to 3.78 kg·hm−2·°C−1, and the annual precipitation production efficiency by 4.55 kg·mm−1·hm−2 to 7.20 kg·mm−1·hm−2. Considering the yields, resource-use efficiency, and economic benefits, the triple-cropping planting patterns show promise as multi-crop systems to achieve high yields and high resource-use efficiency in the Yangtze River Delta region. These results demonstrate the use of a new relay intercropping planting pattern for use in crop production and represent a theoretical contribution to the development of efficient agricultural production.